Numerical Study of Particle Heating in a Plasma Jet - Essiptchouk, A. [UNESP]; Petraconi, G.; Caliari, F. R.; Miranda, F. S.; Yesipchuk, M.; Petraconi, A. (Springer Nature, 2017)
The motion of particles axially injected into the plasma spray process has been studied using a one-dimensional model. The effect of the initial particle velocity and particle diameter on the final particle velocity and temperature was evaluated. The aim of the work is to optimize the spraying process by defining the favorable particle injection velocity, considering a wide range of velocity and temperature of the plasma jet.
Keywords: cold spray; computer modeling; high-velocity plasma spray; plasma powder spraying; process control